Translocation of phospholipase A2α to apoplasts is modulated by developmental stages and bacterial infection in Arabidopsis - Jung, Jihye; Kumar, Krishna; Lee, Hyoung Yool; Park, Youn-Il; Cho, Hyung-Taeg; Ryu, Stephen B. (Frontiers in Plant Science, 2012)
Phospholipase A2 (PLA2) hydrolyzes phospholipids at the sn-2 position to yield lysophospholipids and free fatty acids. Of the four paralogs expressed in Arabidopsis, the cellular functions of PLA2α in planta are poorly understood. The present study shows that PLA2α possesses unique characteristics in terms of spatiotemporal subcellular localization, as compared with the other paralogs that remain in the ER and/or Golgi apparatus during secretory processes. Only PLA2α is secreted out to extracellular spaces, and its secretion to apoplasts is modulated according to the developmental stages of plant tissues. Observation of PLA2α-RFP transgenic plants suggests that PLA2α localizes mostly at the Golgi bodies in actively growing leaf tissues, but is gradually translocated to apoplasts as the leaves become mature. When Pseudomonas syringae pv.~tomato DC3000 carrying the avirulent factor avrRpm1 infects the apoplasts of host plants, PLA2α rapidly translocates to the apoplasts where bacteria attempt to become established. PLA2α promoter::GUS assays show that PLA2α gene expression is controlled in a developmental stage- and tissue-specific manner. It would be interesting to investigate if PLA2α functions in plant defense responses at apoplasts where secreted PLA2α confronts with invading pathogens.